RANCANG BANGUN SISTEM INFORMASI RANTAI PASOK YANG TERINTEGRASI GUNA MENDUKUNG PENGADAAN BAHAN BAKU DI PT. XYZ - Djunita Simatupang; Dadang Surjasa (JURNAL TEKNIK INDUSTRI, 2012)
PT. XYZ is a company engaged in the chemistry sector. PT. XYZ which located in Cikarang industrial area currently has 200 people of employees with the increament in the production and income for the recent years. This situation means company require to improve management and supervision from the management in order to get the production and income increamentoptimized. Accordingly to this, the needs of company management based on integrated supply chain system becoming important.To date, although the current system mostly using computers, there are still different application in some of computers. Unintegrated system cause the double data input which make the process and output result ineffective and inefficient. The application of integrated system hope will support the service activity specially providing information with quick, precise,accurate, and controlled. Integrated information system here defined as a system consist of various component ofdata, application, and technology which related each other to support the information needs of the company. This research using literature, data collection, data analysis, data flow diagram, entity relationship management, specification process, application implementation, andapplication trial. The problem solving including this step: problem identification, objective formulation, inventoring, compile and analysis, and the design method of integrated supplychain information system.